Invective lexis as a means of expressing verbal agression (based on english periodicals) - I. Abramova, Olga (2019)
The present article reveals injective vocabulary as a means of expressing verbal aggression (on the material of the Independent, The Times, The Guardian periodicals, as well as in Internet comments on news and articles). The analysis of articles with injective vocabulary was carried out by the method of continuous sampling. The relevance of this article is due to the fact that in the sociolinguistic aspect verbal aggression is considered as a consequence of the unfavorable sociocultural position in society, growth of asociality, general decline in the level of speech culture, vulgarization of speech, propaganda of violence in the media, a significant weakening of communication and going online. The author reveals the essence of verbal aggression as a sociolinguistic phenomenon, cites the positions of the authors: A.D. Vasilyeva, T.A. Vorontsova, O.S. Korobkova, Z. D Popova, I. A Sternina, Ya. L. Fedorova, N. S. Yakimova, Barbieri F., Dong N., Cornips L., Inkpen D., Luzón, MJ, Ricoeur P., Saggion H., Shaffer K., Sumath C., Trieschnigg D., Volkova S., Yea Jang J. The author proposes a grouping of actual invective vocabulary: 1) Internet jargon; 2) vocabulary, indicating the inferiority of various kinds (verbalization of physical or spiritual impairment); 3) physiological deficiencies in the satisfaction of the natural needs of the person, as well as organs and parts of the body; 4) the opposition "yours is a stranger"; 5) offensive nominations for people based on race, nation (division into "white" and "black", true British and Europeans); 6) courses; 7) statements threatening life and health. The author provides examples of offensive language in the English media for each group. Special attention is paid to ethnopolitics. In the examples, the author focuses on evaluative interjections and particles, familiar references, colloquial expressions, colloquial vocabulary, reduced style vocabulary, and offensive nominations and exaggerations. The author comes to the conclusion that injective vocabulary, which has mobility and dynamism as a level of the language system, communicative and cognitive functions, represents, on the one hand, a verbal form of expressing the aggressive behavior of a person, on the other hand, a means of destructive influence on the interlocutor.